Dementia Reported Missing: Use of an Online Search Engine to Track Outcomes in Persons With Dementia Reported Missing. (April 2019) - Lissemore, Frances M.; Shatzman, Stephanie; Clark, Nicholas; Nash, Jessica; Miller, Rachel; Lerner, Alan J.
Abstract : Background: Persons with dementia (PWD) reported missing are known to be at high risk for mortality. Analysis of online search engines' reports of missing PWD may show patterns in the data of this relatively common event and the broad patterns relevant to mortality risk factors. Methods: We searched Google news for PWD reported missing for 2015. Demographics, personal details, and outcomes were recorded. Results: Of 673 cases, 67 were found deceased, 525 alive, and the remainder had unknown outcomes. Mortality did not differ significantly by race/ethnicity for cases with known outcomes, but cases with unknown outcomes were significantly overrepresented among non-Caucasians ( P <0.001; analysis of variance). Duration missing predicted mortality ( P <0.001; χ 2 ), and mortality was lower if a photograph was provided ( P <0.05; χ 2 ). Five states had no reports and some appeared to have fewer reports that would be expected based on estimates of dementia prevalence. Conclusions: Duration missing was the strongest predictor of mortality. Likelihood of mortality was not predicted by use of missing person alerts, and this may be a consequence of inconsistent reporting and follow-up of cases across states. Prevalence and mortality may likewise be underestimated because of the variability in usage and reporting of relevant search terms and definitions. Online resources and social media can provide information about trends and outcomes related to missing persons with dementia, but greater consistency is needed in definitions, searching, and reporting.